Antecedents And Outcome Of UAE Citizen Satisfaction Of Egovernment Services - Almandoos, Alblooshi Tareq Abbas Ali (2022)
This study investigates the trends in citizen satisfaction with e-government services as observed through service usefulness, service ease of use, information awareness, and service quality. Furthermore, this study investigates the impact of citizen satisfaction towards e-government services on Egovernment service continuance intention.